Small Incision Lenticule Extraction for Postkeratoplasty Myopia and Astigmatism - Tamer H. Massoud; Osama Ibrahim; Kitty Shehata; Moones F. Abdalla (Journal of Ophthalmology)
Purpose. To evaluate the visual and refractive outcomes after small incision lenticule extraction (SMILE) for treating myopia and myopic astigmatism after penetrating keratoplasty (PKP). Design. Case-series. Methods. Ten eyes of 10 patients with previous PKP and residual myopic astigmatism for whom pentacam imaging and thickness measurements were acceptable for laser vision correction. Manifest refraction (MR), uncorrected distance visual acuity (UDVA), and corrected distance visual acuity (CDVA) were obtained preoperatively and one day, one week, and one, 3, and 6 months postoperatively. Cases were operated on the VisuMax® femtosecond laser platform with 500 kHz repetition rate. Results. The mean correction ratio for spherical errors was 0.84±0.19 D and for the mean refractive spherical equivalent (MRSE) was 0.79±0.13 D. Vector analysis showed a mean astigmatism reduction at the intended axis of 67±25.25%, a correction index of 0.81±0.21, and an overall mean percentage of success of astigmatism surgery of 53±37.9%. The postoperative MRSE was stable throughout the 6-month follow-up period. The efficacy index was 0.93 and the safety index was 1.12. Conclusion. SMILE for correction of post-PKP myopia and astigmatism is effective, safe, and stable with moderate accuracy and predictability. Centration of the treatment within the grafts was easily performed.